Phase angle as a predictor of prolonged length of hospital stay and adverse outcomes in elderly medical inpatients: a retrospective cohort study - Liu, Jia; Hu, Song; Wang, Shan; Luan, Tongxiao; Duan, Yuting; Zhou, Jing; Jia, Li; An, Nina; Mao, Yongjun (Frontiers in Nutrition, 2025)
ObjectivesEvaluating prognosis in geriatric inpatients presents significant complexity and challenges. The aim of this retrospective study was to investigate the association between phase angle (PhA) and clinical outcomes in hospitalized elderly patients, specifically focusing on prolonged hospital stays, one-year readmission, or all-cause mortality.MethodsThe study enrolled individuals aged ≥65 years hospitalized in the geriatric medical ward of our hospital. PhA was assessed using BIA, and the length of hospital stay (LOS) was documented. Readmission and mortality outcomes were extracted from electronic medical records and supplemented by telephone follow-ups with patients or their relatives within 1 year following discharge. Optimal PhA thresholds for out-come prediction were determined using Receiver Operating Characteristic curve (ROC). Multivariable Cox proportional hazards regression was employed to evaluate the relationship between PhA and the composite endpoint of readmission or mortality, whereas logistic regression examined its association with LOS.ResultsThis study enrolled a total of 218 geriatric patients over a median follow-up duration of 1 year. Among these participants, 42 patients (19.3%) experienced composite endpoint events, defined as either one-year readmission or all-cause mortality. Adverse event rates across the PhA tertiles (T1–T3) were 32.9%, 18.6%, and 5.6%, respectively, indicating a significant decrease in event incidence as PhA values increased. Multivariable-adjusted Cox regression analysis revealed that low PhA was significantly associated with a higher risk of one-year composite endpoint events (HR = 3.657, 95% CI: 1.625–8.229). Additionally, patients with low PhA based on the optimal ROC-derived cutoff had 3.243 times higher odds of prolonged LOS (95% CI: 1.146–9.177).ConclusionLow PhA is independently associated with prolonged LOS and higher one-year adverse outcomes in elderly medical inpatients. PhA can serve as a valuable indicator for monitoring malnutrition in hospitalized elderly patients and functions as a reliable independent predictor of prognosis.